Searching for lost worlds Tutankhamen - Wheeler, Chris; Fike, Bill; Manuel, Steven; Hutchinson, Sonny (Discovery Communications, 1999)
Witness the story of the richest archaeological find of all time: the Tomb of Tutankhamen, and the two men who made it possible -- Howard Carter and Lord Carnarvon. In 1922, they found the untouched tomb of King Tutankhamen. This episode illustrates the entire process of excavating the tomb, including Lord Carnarvon's sudden and strange death, which led to the widespread belief in the curse of Tutankhamen.